Diskursanalytische Geschlechterforschung in der Erziehungswissenschaft (Jahrbuch erziehungswissenschaftliche Geschlechterforschung, 2021)
Post-structural and discourse-theoretical approaches are of increasing importance for gender research in education and go hand in hand with the increasing use of discourse-analytical methods. The contributions in the volume take up the spectrum of topics that are dealt with, but also provide impulses for systematizing reflections on various theories of discourse and subjectivation and methodological approaches.